2019
DOI: 10.3390/en12173218
|View full text |Cite
|
Sign up to set email alerts
|

Research on Switching Interconnection Modes and Game Control of Interconnected Air Suspension

Abstract: To solve the contradiction between handling stability and ride comfort of vehicles with interconnected air suspension system (IASS) and reduce the energy consumption of air suspension with adjustable spring stiffness, a coordinated control for dynamic performance was designed based on the logic of switching interconnection modes and game control for the damper. The control system consists of a switching controller for air suspension interconnection modes and a distribution controller for the damping force. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Recent studies have shown this index is able to reveal the deviation of responses. 29 A lower value of J X represents a better suspension damping performance.…”
Section: Assessment Manoeuvresmentioning
confidence: 99%
“…Recent studies have shown this index is able to reveal the deviation of responses. 29 A lower value of J X represents a better suspension damping performance.…”
Section: Assessment Manoeuvresmentioning
confidence: 99%
“…In addition, several control strategies were proposed for reducing the power consumption variable setting suspension systems. Specifically, in the paper titled "Research on Switching Interconnection Modes and Game Control of Interconnected Air Suspension", the authors introduced a novel control system for interconnected air suspension systems based on the logic of switching interconnection modes and game control for the damper [18]. It includes a switching controller for air suspension interconnection modes and a distribution controller for the damping force; the first determines the optimal IASS mode dynamically, calculating the vehicle dynamic performance index in real-time.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…The researchers studied the roll, 13–15 pitch, 16,17 elimination torsion, 18 and vibration isolation characteristics 19,20 and stability 21,22 in the air suspension field. Energy saving is a goal for many scholars in different fields of automotive engineering such as the transmission system, 2326 driving cycle, 2729 suspension system, 3032 magnetorheological dampers, 33 energy harvesting, 34 and so on. Sun et al 30 declared that the interconnected system causes energy reduction due to not using compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The game rules can decide how interconnected solenoid valves switch on/off. 30 The commands depend on the dynamical performance of the vehicle and air spring pressure, as it is depicted in Figure 7. The initial rules are given in Figure 7, so by trying different values are given in Table 3 and considering a cost function according to equation (14), the best variables are obtained.…”
Section: Introductionmentioning
confidence: 99%